2017
DOI: 10.1038/s41598-017-00311-8
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of postoperative pancreatic fistula in patients after distal pancreatectomy: a systematic review and meta-analysis

Abstract: Postoperative pancreatic fistula (POPF) is a common complication following distal pancreatectomy (DP). However, the risk factors of this complication in patients after DP still remain controversial. The aim of our study is to estimate the association between potential risk factors and POPF. Relevant articles published up to June 21, 2016 were identified via PubMed, EMBASE, Web of Science, and The Cochrane Library. Studies that examined the risk factors of POPF following DP were enrolled. 20 articles (2070 pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
68
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(73 citation statements)
references
References 37 publications
2
68
1
2
Order By: Relevance
“…For our group of patients, statistical data showed that age is not a risk factor (with an average age of 59.93 years for those without fistula and 53.29 for those with fistula, p = 0.173) Also in a meta-analysis performed on 10 large patient trials, only one study found an increase incidence of pancreatic fistula in older patients [7]. Table 3 Table 2 Table 4 The relative risk for patients receiving Sandostatin is RR = 2.03, which means that these patients have a twofold risk of developing pancreatic fistula.…”
Section: Results and Discutionsmentioning
confidence: 58%
See 2 more Smart Citations
“…For our group of patients, statistical data showed that age is not a risk factor (with an average age of 59.93 years for those without fistula and 53.29 for those with fistula, p = 0.173) Also in a meta-analysis performed on 10 large patient trials, only one study found an increase incidence of pancreatic fistula in older patients [7]. Table 3 Table 2 Table 4 The relative risk for patients receiving Sandostatin is RR = 2.03, which means that these patients have a twofold risk of developing pancreatic fistula.…”
Section: Results and Discutionsmentioning
confidence: 58%
“…An explanation of an incidence of only 15.59% of the pancreatic fistula may be due to the fact that our study group was performed only on patients with malignant pathology. There are studies concluding that malignant tumors are associated with a low risk of fistula [7,8].…”
Section: Results and Discutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Procedure-related factors include anastomotic technique, operation time, and intraoperative blood loss. Of them, numerous studies consistently indicated that pancreatic texture is the most contributory predictor of POPF [28,[30][31][32]. Several meta-analyses reported that patients with soft pancreas have the significantly higher incidence of POPF than did those with hard pancreas [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Of them, numerous studies consistently indicated that pancreatic texture is the most contributory predictor of POPF [28,[30][31][32]. Several meta-analyses reported that patients with soft pancreas have the significantly higher incidence of POPF than did those with hard pancreas [32,33]. Soft pancreas has poor suture holding capacity (SHC) and is frequently associated with parenchymal tearing arising from technical difficulties [31,34].…”
Section: Introductionmentioning
confidence: 99%